Biochemistry in the lab : a manual for undergraduates - Lasseter, Benjamin F. (Boca Raton, Florida : CRC Press, 2020)
"Biochemistry in the Lab: A Manual for Undergraduates presents a comprehensive approach to modern biochemistry laboratory teaching together with a complete experimental experience, from molecular biology, cloning, and protein expression, to purification and characterization"--
OCLC-licensed vendor bibliographic record.
Keywords: Biochemistry -- Laboratory manuals; MEDICAL / Biochemistry; SCIENCE / Chemistry / Analytic; SCIENCE / Chemistry / Organic